A first case report of hypohidrotic ectodermal dysplasia from Oman. Issue 4 (29th February 2020) - Al‐Araimi, Musallam; Hamza, Nishath; Al Hosni, Aliya; Al Mazrooey, Hiba
Abstract: This is a first case report of a patient with hypohidrotic ectodermal dysplasia from Oman, who was found to carry a mutation in the EDAR gene after candidate gene selection based on regions of homozygosity in his genome. Abstract : This is a first case report of a patient with hypohidrotic ectodermal dysplasia from Oman, who was found to carry a mutation in the EDAR gene after candidate gene selection based on regions of homozygosity in his genome.